(3GdeMGSHI aj TQcGJ GdJCejf hGdHfhc GdJLGQjI (B:s (3JCUjd Ydej(B-(3JWHjb Yedj (B/s - (3GdSLGYj, eMehO eMehOs ((3GdbGgQI(B: s (3GdecJHI GdYUQjI(B, s, 2007)
(3GdJGejf (B:-(3GdGSS GdafjI hGdGOGQjI hGdeMGSHjI(B-(3GdeMGSHI Yf YedjGJ JCejfGJ GdMjGI hJchjf GdCehGd(B-(3GdeMGSHI Yf YedjGJ GdJCejfGJ GdYGeI(B-(3GdbhGFe GdeGdjI aj GdefTBJ GdJCejf(B-(3Jbjje COGA efTBJ GdJCejf(B-(3GWGQ acQi ebJQM(B. (3GdHfhc (B:-(3GdfXGe GdeMGSHj aj GdHfhc GdJLGQjI(B-(3JSLjd Cge GdYedjGJ GdeUQajI aj GdOaGJQ hGdSLdGJ(B-(3ELQGAGJ eMGSHI GdJcGdja aj GdHfhc GdJLGQjI(B-(3GdeMGSHI GdGOGQjI aj GdHfhc GdJLGQjI(B-(3MhceI GdHfhc(B-(3GdbhGFe GdeGdjI aj GdHfhc GdJLGQjI(B-(3GdHfhc GdESdGejIs
Keywords: (3Hfhc JLGQjIs; (3TQcGJ GdJGejfs; (3eMGSHIs